Color performance and near infrared reflectance property of novel yellow pigment based on Fe2TiO5 nanorods decorated mica composites. (November 2017) - Gao, Qiang; Wu, Xiaomei; Fan, Yueming; Meng, Qinglin
Abstract: To obtain cool yellow pigments with high near-infrared reflectance, mica/Fe2 TiO5 composite pigments were synthesized by a chemical liquid deposition method. The developed composite pigment powders were characterized by X-ray diffraction (XRD), scanning electronic microscopy (SEM), X-ray photoelectron spectroscopy (XPS), UV–vis–NIR diffuse reflectance spectra, and CIE L*a*b* color scales. Different sized Fe2 TiO5 nanorods were coated on the surface of mica particles. The particle size of the nanorods increased with increasing molar ratio of Fe 3+ to Ti 4+ . The obtained composite pigments showed strong ultraviolet shielding ability and high near-infrared reflectance property. What's more, the Fe2 TiO5 coating with smaller particle size possessed higher reflectance in the region of 700–1500 nm in accordance with the Kubelka-Munk theory. The near-infrared solar reflectance of mica/Fe2 TiO5 composites was as high as 80.3%. An approximately 3 °C decrease in interior temperature was obtained for the heat box coated with the composite pigments. Furthermore, the composite pigments exhibit brilliant yellow colors. Therefore, mica/Fe2 TiO5 composites are excellent near infrared reflective yellow pigments for efficient solar reflective coatings. Highlights: The mica/Fe2 TiO5 composite pigments exhibit brilliant yellow colors. Different sized Fe2 TiO5 nanorods were coated on the surface of mica particles. The NIR solar reflectance of the composites was as high as 80.3%. The composite pigments exhibit strong UV shielding property.